Analisis Kecapaian Belajar IPS Pada Peserta Didik Dalam Pemahaman Materi - Nur Anisa Simbolon, Febrianti Hutagalung, Feby Adelia Parhusip, Salwa Sabrina, Rizal Sanusi Hasibuan (Journal of Educational Research and Humaniora (JERH), 2023)
Social Science Education (IPS) has an important role in this regard. However, so far the social studies learning process has placed more emphasis on the knowledge dimension. Lack of attention to the dimensions of thinking skills. Therefore, in learning with a new paradigm it is hoped that the dimensions of thinking skills will be explored more. With a learner-centered process skills learning approach. Social Science Education (IPS) has an important role in this regard.The purpose of social studies learning is for students to have the ability to understand concepts related to people's lives and have important skills in the midst of world developments to be able to contribute to creating better living conditions. The research method used in this study was the library research method. research. The results of the study show that in understanding social studies material, teacher strategies are needed in overcoming learning difficulties of students in social studies subjects. Strategy is a pattern, a strategy that is planned and determined intentionally to carry out activities or actions in learning and outside learning.